Analisis Pengaruh Citra Merk, Kualitas Produk dan Loyalitas Konsumen Terhadap Keputusan Pembelian Mobil Honda HR-V Di Solo Raya - Sofiyanto, Arif Sholeh, Drs. M. Farid Wajdi, MM.,Ph.D (2016)
The automotive industry in Indonesia is increasing, and has developed very rapidly, various car industry issued their latest product. This led to increasing fierce competition in the automotive industry in Indonesia. The producers are trying to innovate but still meet consumer demand. One company that introduced the Honda, with products HR-V car. HR-V is a car Crosover Utility Vehicle incurred Japan car manufacturer. The purpose of the study was to observasy the effect of brand image, product quality and loyalty of consumer Honda on consumer purchasing decision. Associative research methods with multiple linear regression analysis techniques. The study population amounted to 60 consumers, the sampling technique used accidental sampling where the sampel 60 respondents were calculated using the formula slovin. The result showed simultaneous brand image, product quality, and loyalty consumer have a positive and significant on purchase decisions. The management company should beable to keep product image that has been know to the consumer by maintaining, improving quality and keeping a good relationship to cunsumers are loyalty.